How do the traits of macroinvertebrates in the River Chanchaga respond to illegal gold mining activities in North Central Nigeria - Edegbene, Augustine O.; Elakhame, Luckey A.; Arimoro, Francis O.; Osimen, Ekikhalo C.; Edegbene Ovie, Tega T.; Akumabor, Ehi C.; Ubanatu, Nididi C.; Njuguna, Carolyne W.; Sankoh, Abdul A.; Akamagwuna, Frank C. (Frontiers in Ecology and Evolution, 2023)
The vast mineral reserves in Africa (30% of global mineral reserves) are essential to the continent's development and modern industrial society. However, these minerals, including gold, are often illegally mined by locals which leads to biodiversity loss and groundwater and surface water contamination. In the present study, we assess the impact of illegal gold mining (i.e., panning) and other anthropogenic activities on the distribution of macroinvertebrate traits in the River Chanchaga, North Central Nigeria. We selected four sampling stations (i.e., reaches), that varied in anthropogenic disturbance intensity (Station 1< Station 2< Station 4< Station 3). Four macroinvertebrate traits, body size, mode of respiration, mode of locomotion, and body shape, were selected and categorized into 19 attributes. The trait attributes were assigned to taxa using a fuzzy coding method. The relative abundance of traits in the study river showed that very large body size (>40-80 mm) macroinvertebrates dominated Stations 1 and 2 while large body size (>20-40mm) dominated Station 3. The relative abundance of macroinvertebrates possessing an integument for oxygen diffusion dominated Station 4. The RLQ model showed that traits such as medium body size (>10-20 mm), gills as mode of respiration, and streamlined and spherical body shapes were positively associated with Stations 1 and 2. Conversely, small (>5 -10 mm) and very large (>40-80 mm) body sizes, spiracle: vegetative respiration using plant stems, climbing mode of locomotion, and sprawling mode of locomotion were positively associated with Stations 3 and 4. The fourth-corner test revealed that macroinvertebrates with very small (<5mm) and medium body sizes (>10-20 mm), spiracles mode of respiration and climbing mode of locomotion were positively associated with at least one of the following physico-chemical variables: 1) electrical conductivity [EC (μScm −1 )], 2) biological oxygen demand [BOD 5 (mgl −1 )], 3) sulphate (mgl −1 ), 4) nitrate (mgl −1 ) and 5) phosphate (mgl −1 ). These traits were classified as resilient traits to pollution in our study. On the other hand, macroinvertebrates that possess gills and can swim actively were positively associated with dissolved oxygen and were deemed vulnerable to pollution.